The Legal Gender Asymmetry in the Decisions of the Supreme Court of Justice of the Nation in Mexico - Uribe Bustamante, Diego Enrique (2024)
This paper aims to analyze the tendency of public power in Mexico to integrate gender stereotypes, deeply rooted in Mexican society, into the legal framework and judicial practice. When embedded in the law, these stereotypes perpetuate and even exacerbate inequality between men and women, particularly hindering the enjoyment and exercise of women's rights. Utilizing the hermeneutic method, we interpret and understand the concepts of gender, legal asymmetry, the constitutional principle of equality and non-discrimination, and their relationship with judicial practice. This work identifies the relationship between legal gender asymmetry and gender stereotypes, generating an interesting debate on the meaning of various rulings by the Supreme Court of Justice of the Nation and how these contribute to the realization of formal and material equality between men and women.